Core-Shell Co/CoO Integrated on 3D Nitrogen Doped Reduced Graphene Oxide Aerogel as an Enhanced Electrocatalyst for the Oxygen Reduction Reaction - Wang, Meng; Hou, Yuyang; Slade, Robert C. T.; Wang, Jiazhao; Shi, Dongqi; Wexler, David; Liu, Huakun; Chen, Jun (Frontiers in Chemistry, 2016)
Here, we demonstrate that Cobalt/cobalt oxide core-shell nanoparticles integrated on nitrogen-doped three-dimensional graphene architecture (Co/CoO-NG) were synthesized through a facile hydrothermal method following by heat treatment. The unique endurable porous structure could provide sufficient mass transfer channels and ample active sites on Co/CoO-NG to facilitate the catalytic reaction. The synthesized Co/CoO-NG was explored as an electrocatalyst for the oxygen reduction reaction, showing comparable oxygen reduction performance with excellent methanol resistance and better durability compared with Pt/C.